Spread of the novel vancomycin-resistant Enterococcus faecium strain ST1299/vanA from local level in Germany to cross-border level in Austria, 2018 to 2022 - Wulf Schneider-Brachert (Eurosurveillance)
Introduction Vancomycin-resistant Enterococcus faecium (VREfm) isolates of sequence type (ST)1299 were described recently in south-eastern German hospitals and rapidly expanded from local to cross-border level. Aim We describe the spread of the novel VREfm strain ST1299/vanA on a genetic, geographical and temporal level during the first 5 years after its detection. Methods At University Hospital Regensburg (UHoR), routine VREfm surveillance is whole genome sequencing-based (≥ 1 VREfm per van-genotype, patient and year). In this observational cohort study, we analysed one VREfm ST1299 isolate from our database (2016–2022) per patient and year. Isolates were added from the Hospital of the Merciful Brothers Regensburg (MBR), the National Reference Centre for Staphylococci and Enterococci (NRC), and clinical isolates from Austria. Results We identified 635 VREfm ST1299 isolates (100% vanA), including 504 from Regensburg, and 113 blood cultures. ST1299 isolates were first detected in 2018 simultaneously in Regensburg (n = 2) and southern Bavaria (n = 2), with local (UHoR) and regional numbers increasing rapidly from 2020, shifting to national scale in the same year. Genome data, analysed by cgMLST, showed a predominance of ST1299/CT1903 (315/504 isolates, 62.5%) and ST1299/CT3109 (127/504 isolates, 25.2%) isolates from Regensburg. By 2021, ST1299/CT1903 reached Upper Austria causing hospital outbreaks (n = 5). Phylogeny analysis suggests common ancestors with VREfm ST80, ST18 and ST17. Conclusion Since their emergence in 2018, two highly transmissible subtypes of ST1299/vanA reached national, then cross-border scale. The observed outbreak tendency may explain the rapid and successful spread and the high clonality in our collection.